Training on Healthy Meatball Production and Packaging for Meatball MSME in Medan Helvetia - Nurjama'yah Br. Ketaren; Usman Budi; Ade Trisna (Talenta Publisher, 2025)
Meatballs are widely produced by MSME and contain high nutritional value, making them popular among the community. Meatballs have a short shelf life at room temperature; therefore, many meatball producers use synthetic preservatives and flavor enhancers. This community service activity aims to provide assistance to meatball MSME on producing healthy meatballs and proper packaging, thereby increasing sales and improving the economy. The methods used in this activity include: (1) counseling on the importance of using natural preservatives derived from spices for health, (2) training on producing healthy meatballs using marination technology with garlic extract and other natural food additives to improve meatball quality, (3) training on meatball packaging by labeling containers according to the type of meatball, and (4) assistance and monitoring . The results of this activity show that meatball MSME partners and counseling participants gained knowledge about the negative health impacts of using synthetic preservatives and flavor enhancers. The partners also learned how to produce healthy meatballs using marination technology with garlic extract and proper packaging to improve product quality, increase sales, and boost the economic performance of meatball MSME. Assistance and monitoring results indicate that the partners are highly interested in applying the outcomes of this community service activity to their meatball businesses.